MORPHOLOGICAL ANALYSIS AND BANKLINE SHIFTING OF THE PADMA RIVER NEAR NARIA UPAZILA USING REMOTE SENSING AND GIS TECHNIQUES - MIM, FATEMA RAHMAN; AREFIN, MD. MUKTADIR (My University, 2023)
A river is defined as any naturally occurring body of water that moves along a specified course. Erosion, sediment transport, and sediment deposition are the three most essential processes taking place in river channels. The geography of Bangladesh is largely shaped by its rivers. The Padma is one of the longest rivers in Bangladesh and it goes all the way across the nation. The river's structure is quite dynamic. Currently, riverbank erosion in the Padma River is a significant concern. Naria, located in the Shariatpur district was selected as the research area. This study aims to assess the morphological alterations along the Padma River in the adversely devastated Naria upazila. Satellite pictures from the past 50 years (1972-2022) were evaluated. In this paper, image processing was accomplished with the use of technologies like EarthExplorer and Geographic Information Systems (GIS). The images of Landsat were collected with the use of EarthExplorer. The results of this research demonstrate that calamities such as riverbank erosion-deposition occur as a result of flooding, sediment transport, and human activity. Massive erosion-deposition was observed in Naria upazila, particularly for the floods that occurred in 1987, 1988, 1998, 2004, and 2007, which were assessed in this study. This catastrophe had a serious influence on a great number of people's lives. It has caused a lot of people to lose their homes and jobs and end up on the streets. Residents in this region are leaving their homes to find better living circumstances due to a lack of sanitation, clean water, healthcare and education. Because of this, the government must promptly adopt strategies that supplement current systems. To stop riverbank erosion and protect people and their way of life, it's important to use both non- structural and structural methods.
MORPHOLOGICAL ANALYSIS AND BANKLINE SHIFTING OF THE PADMA RIVER NEAR NARIA UPAZILA USING REMOTE SENSING AND GIS TECHNIQUES